Oral cancer‐associated fibroblasts predict poor survival: Systematic review and meta‐analysis. (15th July 2019) - Graizel, Diana; Zlotogorski‐Hurvitz, Ayelet; Tsesis, Igor; Rosen, Eyal; Kedem, Ron; Vered, Marilena
Abstract: Objectives: To perform systematic review and meta‐analysis on correlations between cancer‐associated fibroblasts (CAFs) and the risk of death for patients with oral squamous cell carcinoma. Subjects and methods: English literature (1966–2018) was systematically analyzed for studies that immunohistochemically assessed CAF density by alpha‐smooth muscle actin and presented 5 year survival rates by Kaplan–Meier plots. Mean age of patients, proportion of male/female patients, and male/female majority (>50% male/female patients) per study were also collected. Significance level for statistical models was p < 0.05. Results: Meta‐analysis comprised 11 studies/1, 040 patients. Univariate Cox regressions showed that high CAF density was a negative prognostic factor in studies with female and male majority [OR 5.329 (95% CI 3.223–8.811), p < 0.001, and OR 2.208 (95% CI 1.717–2.839), p < 0.001, respectively]. High CAF density with male majority was associated with a more favorable prognosis [OR 0.996 (95% CI 0.979–1.013), p < 0.001]. Multivariate Cox regressions showed that death risk was significantly higher among patients with high CAF density compared to low CAF [OR 2.741 (95% CI 2.220–3.384) p < 0.001]. High mean age and male proportion were significantly protective [OR 0.940 (95% CI 0.925–9.955), p < 0.001, OR 0.125 (95% CI 0.018–0.867), p = 0.035), respectively]. Conclusions: CAFs increased death risk, male majority, and higher mean age were protective. A clinically validated cutoff for CAF density could serve as a reliable prognostic tool.